2016
DOI: 10.18632/oncotarget.9495
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate ameliorates radiation-induced acute skin damage in breast cancer patients undergoing adjuvant radiotherapy

Abstract: There are few effective treatment options for radiation-induced dermatitis in breast cancer patients. We conducted a single-arm trial to tested the hypothesis that topical epigallocatechin-3-gallate (EGCG) is effective against radiation-induced dermatitis in breast cancer patients undergoing radiotherapy. Forty-nine patients participated in this study. The patients underwent mastectomy followed by adjuvant radiotherapy. Topical EGCG was applied daily, starting when grade I dermatitis appeared and ending two we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…The adverse reactions of eGcG were found to be mild in the dose expansion test of patients with estrogen receptor-negative breast cancer, and the main adverse reactions included nausea, heartburn, abdominal pain, headache, dizziness and myalgia (59). In stage iii non-small cell lung cancer treated with radiation and chemotherapy, and patients with breast cancer with neoadjuvant radiotherapy, giving eGcG was reported to be safe, and eGcG prevented radiation and chemotherapy injury, playing a positive role in promoting tissue repair (60,61). These clinical trials of eGcG have shown its low toxicity and wide margin of safety.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse reactions of eGcG were found to be mild in the dose expansion test of patients with estrogen receptor-negative breast cancer, and the main adverse reactions included nausea, heartburn, abdominal pain, headache, dizziness and myalgia (59). In stage iii non-small cell lung cancer treated with radiation and chemotherapy, and patients with breast cancer with neoadjuvant radiotherapy, giving eGcG was reported to be safe, and eGcG prevented radiation and chemotherapy injury, playing a positive role in promoting tissue repair (60,61). These clinical trials of eGcG have shown its low toxicity and wide margin of safety.…”
Section: Discussionmentioning
confidence: 99%
“…Additional boluses were added according to chest wall thickness variation. The protocol allowed for a dose variation (in the planning target volume) between 95% and 105% of that at the reference point on the central axis [5][6]. A total dose of 50-Gy radiotherapy was delivered in daily fractions of 2 Gy for five consecutive weeks.…”
Section: Routine Radiotherapy and Assessmentmentioning
confidence: 99%
“…Approximately 87-95% of irradiated patients are characterized by swelling, redness, pigmentation, ulceration, fibrosis, pain, burning and itching of the skin [2][3][4]. RSI has an impact on discomfort and the quality of life of patients [5,6], and may require interference with radiation schedules and complex surgical reconstruction, especially when combined with molecular targeted therapy [7][8][9]. However, evaluation of RSI is not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG) is the main polyphenolic constituent of green tea and is widely recognized as a powerful free radical scavenger. Studies have shown EGCG to be effective in treating several disorders (Zhu et al 2016 ). Specifically, EGCG has demonstrated anti-aging, anti-angiogenic, anti-arthritic, antiviral, anti-inflammatory, and neuroprotective effects.…”
Section: Naturally Occurring Radioprotectorsmentioning
confidence: 99%